Institutional Analysis of Mangrove Rehabilitation in Karangsong Indramayu West Java - Gunawan, Ali Gunawan; Hidayat, Aceng; Anggraini, Eva (Sodality: Jurnal Sosiologi Pedesaan, 2018)
ABSTRACTKarangsong mangrove forest area is the result of rehabilitation since 2008 which is managed and then used as the location of ecotourismby Kelompok Pantai Lestari. The study was conducted in Karangsong Village, Indramayu District, West Java Province. The purposes of this study are to analyze changes in property rights, stakeholders and management institutions of mangrove areas. Data were collected through in-depth interviews of 7 key informants and questionnaires by 96 respondents who were chosen purposively (purposive sampling). This study used qualitative descriptive approach including Property rights analysis, Stakeholder analysis, and Content analysis. The results showed that there has been a change of land ownership status in the mangrove area. Kelompok Pantai Lestari supported by the Karangsong Village government, Diskanla and Pertamina became key actors in mangrove rehabilitation activities.Stakeholder coordination and synergy, as well as local community empowerment needs to be improved to realize sustainable institutions.Keywords : institutional, mangrove, property rights, stakeholdersABSTRAKKawasan hutan mangrove Karangsong merupakan hasil rehabilitasi sejak 2008 yang dikelola dan kemudian dijadikan lokasi ekowisata oleh Kelompok Pantai Lestari. Lokasi penelitian dilakukan di Desa Karangsong, Kabupaten Indramayu, Provinsi Jawa Barat. Penelitianini bertujuan untuk menganalisis perubahan hak kepemilikan lahan, aktor dan kelembagaan pengelolaan kawasan mangrove. Data dikumpulkan melalui wawancara mendalam terhadap 7 orang informan dan pengisian kuesioner oleh 96 responden yang dipilih secara sengaja (purposive sampling). Penelitian ini menggunakan pendekatan deskriptif kualitatif melalui analisis Property rights, analisis Stakeholder, dan Content analysis. Hasil penelitian menunjukkan bahwa telah terjadi perubahan status kepemilikan lahan di kawasan mangrove. Kelompok Pantai Lestari yang didukung oleh pemerintah Desa Karangsong, Diskanla dan Pertamina menjadi aktor kunci dalam kegiatan rehabilitasi mangrove. Koordinasi dan sinergi pemangku kepentingan, serta pemberdayaan masyarakat setempat perlu ditingkatkan untuk mewujudkan kelembagaan yang berkelanjutan.Kata kunci: kelembagaan, mangrove, hak kepemilikan, stakeholders